Evolução de fases durante a hidratação do cimento portland brasileiro por difração de raios x - Gonçalves, Beatriz (2021)
The physicochemical properties of cementitious materials are determined by the mineralogy and hydration process of the cement. In 2018, the ABNT NBR 16697 standard was published, unifying eight standards related to Portland cement. The main changes occurred in the composition, with the increase of the permitted content of the additions. The increase of the addition content in the cement indicated the need of a better understanding of its mineralogy and phase evolution upon hydration. The project aims to understand phases evolution during the hydration of two commercial Portland cements (CP II-F 40) using XRD, focusing on the in situ technique, which had the results compared with the conventional ex situ technique. To understand phases development during hydration, the following methodology were adopted: powdered cements characterization (anhydrous), cementitious pastes characterization with different hydration ages (from 15 minutes to 28 days), in situ and ex situ characterization of the phases progress within hydration. Complementary standardized thermogravimetry analysis (TGA) and compression tests were performed, and the results related to the evolution of phases. The cement with higher alite and aluminate levels showed faster C-S-H and portlandite phase development and more pronounced formation of AFm phases. The ex situ XRD made it possible to quantify the contents of each constituent over time, including amorphous content, and proved to be effective in identifying aluminate hydrates that can affect the performance of CP II-F cements. The in situ method offers time savings, but it is still necessary to develop more accessible approaches for rapid quantification.